2022
DOI: 10.1155/2022/1557010
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Therapeutical Significance of Serpina3n Subsequent Cerebral Ischemia via Cytotoxic Granzyme B Inactivation

Abstract: Ischemic stroke is a devastating CNS insult with few clinical cures. Poor understanding of underlying mechanistic network is the primary limitation to develop novel curative therapies. Extracellular accumulation of granzyme B subsequent ischemia promotes neurodegeneration. Inhibition of granzyme B can be one of the potent strategies to mitigate neuronal damage. In present study, we investigated the effect of murine Serpina3n and human (homolog) SERPINA3 against cerebral ischemia through granzyme B inactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Serpina3n is a murine serine protease inhibitor homologous to the human α1-antichymotrypsin protein. Both Serpina3n and α1-antichymotrypsin can target and inactivate a multitude of proteases; however, unlike α1-antichymotrypsin, SerpinA3n is able to bind to and inhibit extracellular GrB ( Sipione et al, 2006 ; Aslam et al, 2022 ). In murine model of Aortic Aneurysms, systemic Serpina3n treatment was shown to reduce degradation of the proteoglycan decorin while increasing collagen density the aorta of mice, leading to a reduced frequency of aortic rupture and death ( Ang et al, 2011 ).…”
Section: Age-related Diseases In the Eyementioning
confidence: 99%
“…Serpina3n is a murine serine protease inhibitor homologous to the human α1-antichymotrypsin protein. Both Serpina3n and α1-antichymotrypsin can target and inactivate a multitude of proteases; however, unlike α1-antichymotrypsin, SerpinA3n is able to bind to and inhibit extracellular GrB ( Sipione et al, 2006 ; Aslam et al, 2022 ). In murine model of Aortic Aneurysms, systemic Serpina3n treatment was shown to reduce degradation of the proteoglycan decorin while increasing collagen density the aorta of mice, leading to a reduced frequency of aortic rupture and death ( Ang et al, 2011 ).…”
Section: Age-related Diseases In the Eyementioning
confidence: 99%
“…Haptoglobin-related proteins bind to Hb and apolipoprotein-L, which not only link HPR to the cholesterol system, but the HPR/apo-L complex also has a specific trypanosomal lysis effect ( 85 ). SERPINA3 can attenuate neuronal injury by interfering with granzyme B-mediated neuronal death after cerebral ischemia ( 86 ). Presence of SERPINA3N/SERPINA3 aggregates in cortical oligodendrocytes in areas of brain injury ( 87 ).…”
Section: Discussionmentioning
confidence: 99%
“…25 Because the resulting covalent serpinprotease complex is highly stable and resistant to heat, high salt and protein denaturants, detecting its presence by western blot provides a reliable surrogate indicative of Serpina3n/SERPINA3's protease inhibitory function. 26,27 In the alternative substrate pathway, the RCL cleavage is completed efficiently, and the target serine proteases are released, resulting in a cleaved, inactivated Serpina3n/SERPINA3 and an intact, active serine protease protein. The preference of the inhibitory vs substrate pathways is determined by how fast the serpinprotease interaction results in the cleaved conformation and the number of serpins required for inhibiting a single molecule of proteases (stoichiometry of inhibition, SI; greater SI correlates with less effective enzymatic inhibition).…”
Section: Key Pointsmentioning
confidence: 99%
“…Based on this premise, in vitro application of rSerpina3n seemed to slightly but significantly increase the viability of N2a neurons cultured in 'hypoxic medium' by inhibiting granzyme B activity. 27 Recent in vivo data have shown that Serpina3n upregulation in neurons mitigated neuronal injury and loss in ischaemic and traumatic brain injury. [53][54][55]61 These studies suggest that neuronal induction of Serpina3n may represent an endogenous adaptive mechanism to ischaemic and traumatic brain injury.…”
Section: Role and Mechanisms Of Serpina3n/ Serpina3 In Neuronal Death...mentioning
confidence: 99%